Rotavirus RNA polymerase requires the core shell protein to synthesize the double-stranded RNA genome. - Patton, J T (1997)
Rotavirus cores contain the double-stranded RNA (dsRNA) genome, RNA polymerase VP1, and guanylyltransferase VP3 and are enclosed within a lattice formed by the RNA-binding protein VP2. Analysis of baculovirus-expressed core-like particles (CLPs) has shown that VP1 and VP2 assemble into the simplest core-like structures with replicase activity and that VP1, but not VP3, is essential for replicase activity. To further define the role of VP1 and VP2 in the synthesis of dsRNA from viral mRNA, recombinant baculoviruses containing gene 1 (rBVg1) and gene 2 (rBVg2) of SA11 rotavirus were generated and used to express recombinant VP1 (rVP1) and rVP2, respectively. After purification, the proteins were assayed individually and together for the ability to catalyze the synthesis of dsRNA in a cell-free replication system. The results showed that dsRNA was synthesized only in assays containing rVP1 and rVP2, thus establishing that both proteins are essential for replicase activity. Even in assays containing a primer-linked mRNA template, neither rVP1 nor rVP2 alone directed RNA synthesis. Characterization of the cis-acting replication signals in mRNA recognized by the replicase of rVP1 and rVP2 showed that they were the same as those recognized by the replicase of virion-derived cores, thus excluding a role for VP3 in recognition of the mRNA template by the replicase. Analysis of RNA-protein interactions indicated that the mRNA template binds strongly to VP2 in replicase assays but that the majority of the dsRNA product neither is packaged nor stably associates with VP2. The results of replicase assays performed with mutant VP2 containing a deletion in its RNA-binding domain suggests that the essential role for VP2 in replication is linked to the protein's ability to bind the mRNA template for minus-strand synthesis.